Matthew Smolin, Jr.: capstone - Smolin, Matthew, Jr., artist (Colorado State University. Libraries, 2026)
The artist's statement: "Time heals all" is only a half truth. Time also decays memories and removes you each moment from your past. I recapture formative memories as a still moment in time to highlight, accentuate, and prevent erosion. I place the viewer in my scenes, and I allow them the space to play with my imagery by bringing their own interactions with memories, both mine and theirs. Further, I place myself into each of these remembrances through my presence as a part of the moment. Still, I remain at a distance since I can't physically go back into these times. The materials of work change for each memory, a meta commentary on the varied particulars of each moment in time. I challenge viewers to think about the paradoxical nature of presence in memory. I complicate my works by challenging myself to constantly expand my material toolbox. The majority of my materials have already experienced some level of processing before I get to work. Our memories (and my materials) are necessarily human; I highlight human excellence and power by relying on obviously manmade material to build a little world wherein my memory lives.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: sculpture